Update on parasitic dermatoses, - Alberto Eduardo Cox Cardoso; Alberto Eduardo Oiticica Cardoso; Carolina Talhari; Monica Santos (Sociedade Brasileira de Dermatologia, 2020)
Abstract These are cutaneous diseases caused by insects, worms, protozoa, or coelenterates which may or may not have a parasitic life. In this review the main ethological agents, clinical aspects, laboratory exams, and treatments of these dermatological diseases will be studied.